2, 4-Diamino-6-phenyl-1, 3, 5-triazin-1-ium nitrate: intriguing crystal structure with high Z′/Z′′ and hydrogen bond numbers and Hirshfeld surface analysis of intermolecular interactions. Issue 17 (16th April 2021) - Caimac, Nicoleta; Melnic, Elena; Chisca, Diana; Fonari, Marina S.
Abstract : The title compound crystallises in the triclinic centrosymmetric space group P 1̄ with an intriguing high number of crystallographically unique binary salt-like adducts ( Z ′ = 8) and a total number of ionic species ( Z ′′ = 16) in the asymmetric unit. Abstract : 2, 4-Diamino-6-phenyl-1, 3, 5-triazine-1-ium nitrate (LH)(NO3 ) crystallises in the triclinic centrosymmetric space group P 1̄ with an intriguing high number of crystallographically unique salt-like adducts ( Z ′ = 8) and a total number of ionic species ( Z ′′ = 16) in the asymmetric unit. The organic cations and nitrate anions are combined into two similar H-bonded neutral tapes strengthening by 20 unique NH⋯O and NH⋯N hydrogen bonds each. Hydrogen bonds are ordered into a repeated sequence of homo- and hetero-synthons, R22(8)R33(10)R22(8)R22(8)R24(8)R33(10) as ring motifs. The paired cations form R22(8) ring motifs through base pairing of N–H⋯N hydrogen bonds. All other patterns include both cations and anions. In the crystal structure, the compromise between the tapes rigidity provided by the multiple directional H-bonds within the tapes and packing preferences is reached through the restricted internal rotation about the C–C bond joining the phenyl and triazine cycles in the 2, 4-diamino-6-phenyl-1, 3, 5-triazine-1-ium cations. The decisive impact of NH⋯O(N) hydrogen bonds in the crystal stability and distribution of other types of intermolecular interactions was estimated by Hirshfeld surface analysis. The undertaken CSD overview for the metal-free L-based crystals reveals the exclusivity of the title compound from the viewpoint of the high reported Z ′/ Z ′′ values and the number of unique hydrogen bonds.